Drought consistently alters the composition of soil fungal and bacterial communities in grasslands from two continents. (26th March 2018) - Ochoa‐Hueso, Raúl; Collins, Scott L.; Delgado‐Baquerizo, Manuel; Hamonts, Kelly; Pockman, William T.; Sinsabaugh, Robert L.; Smith, Melinda D.; Knapp, Alan K.; Power, Sally A.
Abstract: The effects of short‐term drought on soil microbial communities remain largely unexplored, particularly at large scales and under field conditions. We used seven experimental sites from two continents (North America and Australia) to evaluate the impacts of imposed extreme drought on the abundance, community composition, richness, and function of soil bacterial and fungal communities. The sites encompassed different grassland ecosystems spanning a wide range of climatic and soil properties. Drought significantly altered the community composition of soil bacteria and, to a lesser extent, fungi in grasslands from two continents. The magnitude of the fungal community change was directly proportional to the precipitation gradient. This greater fungal sensitivity to drought at more mesic sites contrasts with the generally observed pattern of greater drought sensitivity of plant communities in more arid grasslands, suggesting that plant and microbial communities may respond differently along precipitation gradients. Actinobateria, and Chloroflexi, bacterial phyla typically dominant in dry environments, increased their relative abundance in response to drought, whereas Glomeromycetes, a fungal class regarded as widely symbiotic, decreased in relative abundance. The response of Chlamydiae and Tenericutes, two phyla of mostly pathogenic species, decreased and increased along the precipitation gradient, respectively. Soil enzyme activity consistently increased under drought, a response that was attributed to drought‐induced changes in microbial community structure rather than to changes in abundance and diversity. Our results provide evidence that drought has a widespread effect on the assembly of microbial communities, one of the major drivers of soil function in terrestrial ecosystems. Such responses may have important implications for the provision of key ecosystem services, including nutrient cycling, and may result in the weakening of plant–microbial interactions and a greater incidence of certain soil‐borne diseases. Abstract : Direct and indirect effects of drought and environmental conditions on bacterial community composition and microbial activity.